(untitled) - Davies, John H. (Oxford, 2008)
The MSP430 microcontroller family offers ultra-low power mixed signal, 16-bit architecture that is perfect for wireless low-power industrial and portable medical applications. This book begins with an overview of embedded systems and microcontrollers followed by a comprehensive in-depth look at the MSP430. The coverage included a tour of the microcontroller's architecture and functionality along with a review of the development environment. Start using the MSP430 armed with a complete understanding of the microcontroller and what you need to get the microcontroller up and running!
Mạng công nghiệp và truyền thông,Kỹ thuật vi điều khiển,Đo lường và điều khiển bằng máy tính
Keywords: Texas Instruments MSP430 series microprocessors,C (Computer program language),Bộ vi xử lý Texas Instruments MSP430,C (chương trình ngôn ngữ máy tính); Programming,Lập trình